Development of a Non-Invasive Method for Monitoring of HV Circuit Breaker Switching Time - Sagar Bhutada (The Indonesian Institute of Science and Technology Research, 2026)
Modern HV circuit breakers may be vulnerable to catastrophic failure as they are designed for higher stress than the earlier CB designs with multiple interrupters per pole. With the advantage of controlled switching, improved performance is obtained for dielectrically well-designed interrupters, which achieve a re-ignition-free window during opening of the CB, in turn minimizing the risk of nozzle puncture. On occasion, asset owners may wish to check whether the CB is performing satisfactorily and whether the controllers are providing reliable and repeatable stress control. Monitoring of voltage waveforms during switching using well-established offline diagnostic methods will provide information about small re-ignitions and re-strikes. However, waveform measurement at moderately high signal frequency would require a CB outage to connect specialized equipment. A non-invasive measurement technique devising re-striking voltage sensors has been developed by the authors to measure high-frequency voltage waveforms occurring during switching operations without the need for an outage. Results of tests performed in the laboratory and 245 kV substation illustrating the capability of this new method to detect re-ignitions are presented in this paper. The proposed diagnostic approach relies on parameters such as operating times, pre-strike characteristics, and restrike detection. Transient electromagnetic emissions have been identified as a promising means to evaluate the above parameters non-intrusively.